Dashboard for Industrial Load Control and Remote Power Factor Correction Based on Adafruit's MQTT - Irgi Surya; Jaja Kustija (Universitas Ahmad Dahlan, 2023)
One of the user interface problems in an internet of things (IoT) system is influenced by monitoring which is easy to access, flexible and efficient in its use, has been discussed a lot but the problem is still unresolved, one solution to this problem is by presenting the Adafruit mqtt, which by using the mqtt Adafruit user interface for monitoring on an internet of things system can facilitate control and remote control. In this case the use of Adafruit mqtt is used to monitor electrical loads and improve power factor. This research presents an internet of things system that is capable of monitoring electrical load and improving power factor that already uses the Adafruit mqtt as its user interface. The method used is through the Analysis, Design, Development, Implementation, Evaluation (ADDIE) approach. The results showed that this system is feasible to use because based on the experimental results this system is able to work well and provide convenience for users and can monitor in real time current, voltage, energy, frequency, power factor, real power, apparent power, and reactive power. only by using smartphones, laptops, tablets, or computers. It is hoped that in the future this research will be able to continue to be developed so that the use of electrical energy in industry can be much more effective and efficient.